2003
DOI: 10.1182/blood-2003-01-0045
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and clinicobiologic characteristics of leukemic B-cell chronic lymphoproliferative disorders with more than one B-cell clone

Abstract: Leukemic B-chronic lymphoproliferative disorders (B-CLPDs) are generally believed to derive from a monoclonal B cell; biclonality has only occasionally been reported. In this study, we have explored the incidence of B-CLPD cases with 2 or more B-cell clones and established both the phenotypic differences between the coexisting clones and the clinicobiologic features of these patients. In total, 53 B-CLPD cases with 2 or more B-cell clones were studied. Presence of 2 or more Bcell clones was suspected by immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
2
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(142 citation statements)
references
References 25 publications
8
127
2
5
Order By: Relevance
“…However, the development of new B-cell subclones resulting from the occurrence of additional genetic mutations in the neoplastic cells during the evolution of the disease has been described [35][36][37], with studies reporting CLL cases with two unrelated B-cell clones [9,[36][37][38][39]. In order to minimize the risk of including such cases in our series of patients with double productive IGHV rearrangements, we checked blood smear morphology and we run a four marker phenotypical panel as a requisite for inclusion in the study in all 60 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the development of new B-cell subclones resulting from the occurrence of additional genetic mutations in the neoplastic cells during the evolution of the disease has been described [35][36][37], with studies reporting CLL cases with two unrelated B-cell clones [9,[36][37][38][39]. In order to minimize the risk of including such cases in our series of patients with double productive IGHV rearrangements, we checked blood smear morphology and we run a four marker phenotypical panel as a requisite for inclusion in the study in all 60 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of a single Ig light chain by CLL B-cells (j or k) was required ( Fig. 1) based on previous studies reporting that biclonality in CLL can be reliably ascertained by flow cytometry, with distinct B-cell populations usually expressing different sIg light chains isotypes [9,36,40,41]. To confirm this assumption in our series, we studied two cases with double IGHV rearrangement where flow cytometry had revealed expression of distinct surface Ig light chain (j and k).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along these lines, it has been reported that up to 5% of patients with B-cell chronic lymphoproliferative malignancies may display two or more clonal populations. 14 In such cases, if two separate tumor populations are indicated by flow cytometry, biclonality can be conclusively proven only after identification of the light chain sequence(s) at the molecular level.…”
Section: Explanationmentioning
confidence: 99%
“…In two CLL cases, a total of three IGK locus gene rearrangements were detected by NGS in each case, raising the possibility of more than one clonal population being present, as previously described in chronic B-cell LPD. 13 Additionally, aberrant clonal rearrangements were seen that were not detected with conventional PCRbased approaches (e.g. IGKV to IGK intron), which warrant further analysis.…”
Section: Letters To the Editormentioning
confidence: 99%